An Analysis Of Conflict Found In The Novel Entitled “It Ends With Us” By Coolen Hoover - Ni Kadek Risa Puspita Padmi; I Gusti Agung Sri Rwa Jayantini (Denpasar Institute, 2022)
The objective of this study is to find out the conflict faced by the main character. This study used a novel by Coolen Hoover entitled It End With Us as the data. The aim of this study was to define the types of conflict faced by the main character. The data were analyzed based on the theory proposed by William Kenney (1996). The data collection technique was observation method and note taking. The observation method was reading the novel intensively and note-taking for the marking the main point of the conflict. After analyzing the data, the researcher found that there are two types of conflict that appeared in Coolen Hoover’s novel they are internal and external conflict. The dominant conflict was the internal conflict. The internal conflict happens between Lily, the main character with her feelings and mind, while the external conflict occurs between Lily and her parentsConflict